Psychological Capital Questionnaire (PCQ-24): Preliminary Evidence of Psychometric Validity of the Brazilian Version - Cid,Daren Tashima (2020)
Abstract The PCQ-24 is the main international measure for assessing psychological capital (PsyCap) in organizational contexts. In order to evaluate its adaptation to the Brazilian context, this study aimed to verify preliminary evidences of its psychometric validity. Data collection was conducted online with 749 employees from all regions of Brazil. Confirmatory factor analysis was performed to examine the quality of fit of the second-order factor structure of PCQ-24. The fit indicators were satisfactory (χ2= 742.10, χ2/df= 4.01, p< .001, SRMR= .05, CFI= .91, GFI= .90, TLI= .90, RMSEA= .06). Cronbach’s alpha was .92 and the composite reliability coefficient was .95; in addition, a multigroup confirmatory factorial analysis, comparing male and female participants, demonstrated that the scale is adequate for both groups. These results indicate, in a preliminary way, the validity of PCQ-24 as a measure of psychological capital in the Brazilian labor context.